Effect of Penile Traction and Vacuum Erectile Device for Peyronie's Disease in an Animal Model. Issue 10 (8th September 2017) - Lin, Haocheng; Liu, Chunhui; Wang, Run
Abstract: Background: Penile traction therapy with the use of a traction device (TD) or vacuum erectile device (VED) has been studied as local modalities for Peyronie's disease (PD). Aim: To identify changes of penile curvature, erectile function, and possible cellular and molecular mechanisms between the TD and VED in a rat model of PD. Methods: Peyronie's plaque was induced in 30 adult male rats. Then, rats were randomly divided into control (PD without treatment), VED, and TD groups. In the VED group, vacuum pressure was applied to the cylinder to induce penile engorgement inside the cylinder for 1 minute. The penis was allowed to deflate completely for another 1 minute. This was repeated for five cycles (inflate and deflate). In the TD group, the rat penis was straightened by a suspended tension gauge at the same tension by clamping the prepuce. This was performed three times per day at 20 minutes per session, with 5-minute intervals between sessions. The entire treatment duration was 4 weeks. Outcomes: Penile curvature, intracavernosal pressure, and mean arterial pressure were measured. Immunohistochemistry for α-smooth muscle actin, transforming growth factor-β1 and mothers against decapentaplegic homolog 2/3 were performed. Results: The TD and VED groups had less penile curvature compared with the control group (15.3 ± 5.3° for TD, 28.4 ± 6.8° for VED, 38.6 ± 10.5° for control; P < .001 for TD vs control, P < .05 for VED vs control). The TD group also had less penile curvature compared with the VED group ( P < .05). The VED group had a higher ratio of intracavernosal pressure to mean arterial pressure compared with the two other groups (0.56 ± 0.10 for VED, 0.38 ± 0.06 for TD, 0.32 ± 0.07 for control; P < .001). The immunohistochemistry results showed the VED group had more preserved α-smooth muscle actin with less transforming growth factor-β1 and mothers against decapentaplegic homolog 2/3 than the TD and control groups in the corpus cavernosa. Clinical Translation: Various benefits can be observed with the TD and VED for the treatment of PD. Strengths and Limitations: This study explored the mechanism and benefits of TD and VED therapies for the treatment of PD. The rat model might not represent the human condition. Conclusion: Penile traction therapy with the TD or VED is beneficial to decrease penile curvature in animal models of PD. The underlying mechanism could be related to antiapoptosis, antifibrosis, and smooth muscle preservation.